Interannual dynamics of the Yellow River turbid plume: the role of the water–sediment regulation scheme - Fujia Wang; Xiaoli Bi; Fanzhu Qu; Tao Zou; Xiao Hua Wang; Ling Meng; Ling Meng (Frontiers in Marine Science)
The water–sediment regulation scheme (WSRS), initiated in 2002, induced an impulse delivery of freshwater and sediment within 10–20 days. In this scenario, the Yellow River turbid plumes (YRPs), which serve as indicators of the marine dispersion of terrestrial materials, displayed substantial spatio-temporal variations. However, the extension patterns of the YRP and their dynamic mechanisms on an interannual scale remain poorly understood. Using multi-source high-resolution imageries, the YRP variations were examined during 2003–2023. The results revealed that the WSRS significantly increased the extensions of the YRP, with its area expanding annually from 67.41 ± 25.27 to 162.54 ± 39.03 km2. Additionally, three distinct diffusion patterns were identified: I) a frequent prototypical spreading along the direction of river channel expansion, II) rightward spreading toward Laizhou Bay, and III) leftward spreading toward Bohai Bay. River discharge was identified as the primary driver controlling the plume extension, followed by wind, which primarily modulated the plume orientations. Furthermore, several unique plume extension patterns were observed under episodic weather events.